Fiscal Illusion and Defining Factors of Capital Expenditure (Study on Undeveloped Areas in West Nusa Tenggara) - Riana Meilya; Akram Akram; Titiek Herwanti (International Review of Management and Marketing, 2018)
The purpose of this study is to verify and find empirical proof on the influence of local revenue, general allocation funds, special allocation funds and profit-sharing funds on capital expenditures. And to detect the occurrence of fiscal illusions on capital expenditure financing. The population is the form of Local Government Financial Report of Fiscal Year 2012 until 2016 of all districts included in undeveloped areas in NTB according to Presidential Regulation No. 131 of 2015. This study takes the entire population as the subject of research (census study). Data analysis technique used is descriptive statistics and F test, t test and R2 test to test the hypothesis by first doing the classical assumption test. The result of classical assumption test shows that normal distributed data, no multicolinearity problem, no autocorrelation, and free data from heterokedastisity problem. The results show that local revenue, special allocation funds and profit-sharing funds have a positive effect on capital expenditure. While for variable of general allocation fund  have negative effect to capital expenditure. There has been a fiscal illusion on capital expenditure financing since there is a variable of general allocation receipt which has a negative correlation with the spending of local government capital expenditures.